(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This lending company started its operations in 2012 and now has seven branches in the Philippines with its head office located at Caloocan City. Its employees consist of 37 regular employees and 24 probationary employees. It has an HR Manager and 2 assistant HR personnel. Since the company is on its early years of operations, the researchers find it beneficial to propose clearly stated procedures, policies on safety and health, contractual arrangements, disciplinary actions, and compensation and benefits. The researchers interviewed the HR Manager and asked carefully structured questions to gather data for the study. The researchers compared the company’s current policies with other companies’ in the same industry to find out best practices that the company may adopt.Current policies of the company include Mobile Policy, Free Internet Policy, Smoking Policy, Anti-Discrimination, Dress Code Policy, Schedule Policy, Record Keeping, Time Keeping, Salary Increase, Rules and Regulations, 13thMonth Pay, Cash Advance, Free Meal, Birthday Allowance, Loyalty Incentives, Legal and Special Holiday, Process of Recruitment, Contractual Arrangement Policy, Safety Policy and Work Arrangement. The company program includes Medical Assistance, Profit Sharing, Company Outing, Physical Wellness and Company Loan. The company also practices Orientation and Team Building. The researchers proposed a total of 22 policies which are; Drug Test Policy, Wearing of ID Card, Anti-Harassment, Nepotism, Application for Leave, Resignation, Data Privacy Act, Government Mandated Benefits, Payroll Deductions Policy, Bereavement Leave, Human Resource Recruitment, Requisition and Planning, Orientation Agreement, Occupational Safety and Health Standards, Training Programs, Process of Promotion, Employee Intervention and Evaluation, Recognition, Persuasive Management Style, Job Description and Strong Implementation of Company Rules and Regulations. Policies developed and enhanced by the researchers may be beneficial for use or reference for the company.